An Efficient Method for Chemoselective Reduction of Nitro Compounds Using Bimetallic Fe‐Ni NPs/H3PW12O40.×H2O System. Issue 10 (7th July 2014) - Rezazadeh, Soodabeh; Akhlaghinia, Batool; Goharshadi, Elaheh K.; Sarvari, Hossein
Abstract The selective reduction of nitro compounds by treatment with bimetallic Fe‐Ni nanoparticles (NPs) and tungestophosphoric acid hydrate (H3PW12O40.×H2O) in H2O is reported. The method has been applied to a broad range of nitro compounds with different sensitive functionalities, including halides, carbonyl, hydroxyl, aldehyde, methyl, acetyl, nitrile, and ester substituents with excellent yields. The reaction yielded single product in all cases with very high yield. The simple experimental procedure and easy purification make the protocol advantageous.